Bioactive compounds, antioxidant activity, and color retention of beetroot (Beta vulgaris L.) powder: Effect of steam blanching with refrigeration and storage. Issue 3 (3rd February 2021) - Kaur, Sehajveer; Kaur, Navjot; Aggarwal, Poonam; Grover, Kiran
Abstract: Beetroot ( Beta vulgaris L.) was subjected to different blanching treatments, that is, T1 (hot‐water blanching with cold water immersion), T2 (steam blanching with cold water immersion) and T3 (steam blanching with refrigeration) for obtaining beetroot powder. Fourier transform infrared spectroscopy was used for the evaluation of functional groups in the different blanching treatments. Fresh beetroot and the sample with maximum functional groups, that is, T3 was further used to analyze chemical composition, betalains content, bioactive compounds, antioxidant activity, and color values. Processing of beetroot resulted in significant increase in all the biochemical as well as color parameters in comparison to fresh beetroot. Total phenols, flavonoids, betalains content, and antioxidant activity of fresh and powdered beetroot increased from 77.88 to 416.65 mg GAE/100 g, 42.75 to 279.95 mg QE/100 g, 677.34 to 2469.07 mg/100 g and 47.69 to 76.54 percent (dry basis), respectively. Color analysis of the samples indicated that with drying, L * value decreased (23.10–21.38) but a * value increased (13.16–13.30) which implies that beetroot powder was having good coloring properties and can be used as natural colorant in foods. Bioactive compounds of beetroot powder significantly decreased but were still beneficial for consumption as even after 3 months of storage beetroot powder contained high amounts of antioxidants. Practical applications: Artificial colorants are extensively available in the market where red color is one of the most widely used colors for the food preparations. Many food industries, caterings establishments, and restaurants prefer artificial colorants with number of chemicals that can bring about detrimental health effects like cancer to the consumer. Having an alternative natural colorant which is safer and health friendly to use is a need of the hour. Keeping this in view, beetroot powder has been developed using a very economical method, that is, steam blanching with refrigeration as a pre‐treatment prior to drying. Beetroot ( Beta Vulgaris L.) in powder form can be potentially used as a natural colorant as an alternative to the artificial colorants being used in the food industry which will not only act as a natural colorant but will also be rich in bioactive compounds like phenols, flavonoids, betalains, and will have a strong antioxidant potential.